ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI WILAYAH MEDAN HELVETIA PELAYANAN SPAM MEBIDANG (MEDAN-BINJAI-DELI SERDANG) - Tanjung, Willyam Han Ardy; Adrian, Muhammad; Zebua, Meiman Restu; Hutabarat, Mulia; Arya, Zikri Vieri; Mulyana, Rachmat; Wardana, Novrizaldi (Jurnal Manajemen dan Bisnis, 2025)
The availability of clean water is a vital aspect in supporting the quality of life of the community, especially in densely populated urban areas such as Medan Helvetia District. This study aims to analyze the projection of clean water needs and availability for the next 50 years, and to assess the balance between the two as a basis for planning clean water infrastructure development. The methods used include calculating domestic and non-domestic water needs, plus an estimate of 30% water loss, and analyzing needs at peak hours and maximum days. The results of the analysis show that with a fixed supply capacity of 1,100 liters per second from SPAM Mebidang, the need for clean water in Medan Helvetia District until 2075 is still in a surplus condition. The highest surplus was recorded at 795.26 liters per second in 2024, and the lowest surplus was 510.77 liters per second in 2075. These findings indicate that the district is projected not to experience a clean water deficit in the long term, as long as the supply capacity remains stable and the distribution system is managed efficiently. Therefore, periodic evaluation and integrated planning are still needed to ensure the sustainability of clean water services in the future.